2018
DOI: 10.1111/joor.12726
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct‐current stimulation reduces nociceptive behaviour in an orofacial pain model

Abstract: Background: Transcranial direct-current stimulation (tDCS) is a noninvasive method of brain stimulation suggested as a therapeutic tool for pain and is related to the reversal of maladaptive plasticity associated with chronic pain.Objectives: This study investigated the effect of tDCS, a non-pharmacological therapy, on local mechanical hyperalgesia, and remote thermal hyperalgesia in rats submitted to orofacial inflammatory pain model, by facial von Frey and hot plate tests, respectively. In addition, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…The current study provides preliminary evidence that tDCS is effective for improving QST measurements in individuals with knee OA. These results are consistent with the limited number of previous studies supporting the role of tDCS for improving QST measurements [26,42,43], primarily in individuals with a variety of chronic pain conditions other than knee OA (e.g., central poststroke pain [44]; orofacial pain [45]; fibromyalgia, chronic migraine, and neuropathic pain [46,47]).…”
Section: Discussionsupporting
confidence: 91%
“…The current study provides preliminary evidence that tDCS is effective for improving QST measurements in individuals with knee OA. These results are consistent with the limited number of previous studies supporting the role of tDCS for improving QST measurements [26,42,43], primarily in individuals with a variety of chronic pain conditions other than knee OA (e.g., central poststroke pain [44]; orofacial pain [45]; fibromyalgia, chronic migraine, and neuropathic pain [46,47]).…”
Section: Discussionsupporting
confidence: 91%
“…Also, chronic systemic inflammation promoted neuroinflammation mainly induced by IL-1β-positive microglia in female rats 44 . A previous study by our research group showed that CFA-induced orofacial pain increased brainstem IL-6 levels and decreased brainstem IL-10 levels, suggesting that the pain model induced an imbalance in the inflammatory system regarding the structure analyzed 45 . Altogether these studies highlight that peripheral CFA injection induces a response of inflammatory signaling in the peripheral and central nervous system.…”
Section: Discussionmentioning
confidence: 76%
“…The first reported study was published in 2012 (Spezia Adachi et al, 2012) (Table 1). Eight of the nine studies were developed by the same research group at the Federal University of Rio Grande do Sul (Callai et al, 2019;De Oliveira et al, 2019;Scarabelot et al, 2019;Cioato et al, 2016;Lopes et al, 2020;Spezia Adachi et al, 2012;Regner et al, 2020;Santos et al, 2020). All nine were scientific articles published in well-known journals, in English, with a predominance of three published in the Journal Brain Stimulation (Spezia Adachi et al, 2012;Cioato et al, 2016;Lopes et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies used bimodal stimulation (Table 1) (Callai et al, 2019;De Oliveira et al, 2019;Scarabelot et al, 2019;Cioato et al, 2016;Lopes et al, 2020;Regner et al, 2020;Santos et al, 2020) and two article used anodal current (Spezia Adachi et al al., 2012;Guo et al, 2020). In addition, the electrode position varied: seven articles used the area between the parietal cortex hemispheres (Scarabelot et al, 2019;Callai et al, 2019;Regner et al, 2020;Lopes et al, 2020;Santos et al, 2020;Cioato et al, 2016;Spezia Adachi et al, 2012), one study on the prefrontal cortex (De Oliveira et al, 2019), and one reported the application on the skullcap (Guo et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation